2011
DOI: 10.1227/neu.0b013e318217141c
|View full text |Cite
|
Sign up to set email alerts
|

“Double-Stick Tape” Technique for Transposition of an Offending Vessel in Microvascular Decompression: Technical Case Report

Abstract: The advantage of our "double-stick tape" technique is the simplicity of the procedure. The present technique is a feasible alternative for the treatment of hemifacial spasm caused by a tortuous VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Kivelev et al 13 retrospectively analyzed 100 consecutive patients who had undergone microneurosurgical procedures utilizing TachoSil and reported that no patient showed any signs of allergic reaction or infection. Microvascular decompression using TachoComb was first described by Ichikawa et al 9 in 2011. TachoSil has several advantages for MVD given its elasticity, ease in manipulating it into various shapes and configurations, and easy application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kivelev et al 13 retrospectively analyzed 100 consecutive patients who had undergone microneurosurgical procedures utilizing TachoSil and reported that no patient showed any signs of allergic reaction or infection. Microvascular decompression using TachoComb was first described by Ichikawa et al 9 in 2011. TachoSil has several advantages for MVD given its elasticity, ease in manipulating it into various shapes and configurations, and easy application.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Experience with this material in MVD was first described in 2011 as the "double-stick tape" technique. 9 We modified this technique to improve ease of handling and performance of TachoSil, which we trimmed and soaked with fibrin glue between thumb and forefinger to create an adhesive material similar to birdlime ( Fig. 1), an adhesive and sticky material smeared on twigs to ensnare small birds.…”
mentioning
confidence: 99%
“…Arteriopexy can be performed using adhesive compositions, 'suspending loops' made of synthetic materials, dural and fascial flaps, microsurgical sutures passed around or through the vascular adventitia, as well as fenestrated aneurysmal clips. 6,11,[13][14][15][16][19][20][21][22][23][24][25][26] The double-stick tape technique for the transposition of an offending vessel in MVD in hemifacial spams was described by Ichikawa et al in 2011. 16 The use of sling/loop fixation of the artery is the most attractive and reasonable way of performing neurovascular decompression, since: the success rate is very high; it eliminates the need to install a large implant; it reduces the chance of developing aseptic granuloma; and it reduces the chance of postoperative neurological complications that occur due to the placement of large implants.…”
Section: Discussionmentioning
confidence: 99%
“…Various modifications in the surgical technique of vascular decompression are used in these cases of tortuous vertebrobasilar artery (TVBA), from the placement of metal implants (between the nerve root and the rigid vessel) to adhesive fixation of the displaced vertebrobasilar artery. [1][2][3][4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the present paper, we describe a new technique to sling a TVBA to the petrous dura for microvascular decompression (MVD) in a patient with hemifacial spasm caused by a TVBA.…”
Section: Introductionmentioning
confidence: 99%
“…Большинство авторов используют тефлоновые имплантаты в виде шариков и комочков, значительным числом которых тампонируют образовавшееся после транспозиции пространство, что обеспечивает надежность фиксации вновь созданных нейроваскулярных взаимоотношений. Предложены разнообразные способы фиксации перемещенной артерии с помощью клеевых композиций, «подвешивающих петель» из синтетических материалов, лоскутов твердой мозговой обо-лочки и фасции, хирургических нитей, проводимых вокруг или через адвентицию сосуда, а также фенестрированных аневризматических клипс [8,13,15,19,21,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48]. Применение петлевой фиксации артерии является наиболее приемлемым способом нейроваскулярной декомпрессии, так как устраняется необходимость установки значительного по размерам имплантата, и снижает вероятность развития асептических гранулем.…”
Section: рис 5 интраоперационные фотографии при тригеминальной неврunclassified